A retrospective study with ICAST-R (ispcan child abuse screening tools-retrospective) questionnaire for determination of child abuse in first year medical students in Turkish population. (July 2017) - Simsek, Erdem; Guney, Sevay Alsen; Baysal, Serpil Ugur
Abstract: Child Abuse and Neglect (CAN) is an important problem both in Turkey and worldwide. Unfortunately, we still don't have enough and reliable data on this important subject. In this study, we aimed to investigate the prevalence of childhood maltreatment in a population of first year medical students in a Turkish university using the retrospective version of the ISPCAN Child Abuse Screening Tool (ICAST-R). One hundred seventy three first year medical students, aged between 18 and 24 years, who agreed to complete the ICAST-R questionnaire, were recruited in our study. Of 173 students who completed the survey, 51.4% are found to be subjected to at least one type of child abuse (physical, emotional or sexual). The prevalence is higher in male gender and the difference is statistically significant. Physical, emotional and sexual abuse exposure rates are found to be 23.1%, 40.5% and 11% respectively. Physical and emotional abuse rates are higher in male gender and the difference is statistically significant. We did not find any statistically significant association between gender and sexual abuse. Efforts to prevent child abuse and neglect are growing in our country, as they are worldwide. However, child abuse is still common and a problematic issue. It is important to determine the prevalence of child abuse in order to raise awareness. We need further studies investigating not only prevalence but also risk factors to have reliable data for our country.